Infertility treatment in autosomal dominant polycystic kidney disease (ADPKD) -: a case report - Orhan, I; Onur, R; Ergin, E; Köksal, IT; Kadioglu, A (Blackwell Wissenschafts-Verlag Gmbh, 2000)
Autosomal dominant polycystic kidney disease (ADPKD) is a frequently occurring inherited condition with cysts in many organs including the kidneys. However, a combination of seminal vesicle cysts, cystic obstruction of ejaculatory duct and ADPKD is rarely encountered. The following case report presents an infertile ADPKD patient who had seminal vesicle cysts and ejaculatory duct cyst, and describes the treatment by transurethral resection of the ejaculatory duct.
Keywords: autosomal dominant polycystic kidney disease; infertility; transurethral resection of ejaculatory duct